Investigating educational policy through ethnography - Walford, Geoffrey (Amsterdam : JAI, 2003)
Within the United Kingdom questions about the relevance of educational research and its relationship to policy have recently been the centre of a prolonged, public and sometimes acrimonious debate.The chapters in this book illustrate the ability of ethnographic work to assist in understanding the effects of educational policies to gradually influence the policy discourse. The book includes studies of policy initiatives at the local level that show the extent to which an intended change actually occurred in practice, others where actual change occurred, but there were unintended consequences as well as those planned by the policy, and others that illuminate the contradictions within the original policy itself. Chapters focus on a diversity of topics such as the ideology of educational 'success', politics and school mathematics, ITC teaching, sports coaching, basic skills provision for offenders, second language learning, ESOL teaching, primary teachers work, and the teaching of reading and spelling.
Includes bibliographical references.
Description based on print version record.
Keywords: Education and state; Educational anthropology; Education -- Political aspects; Ethnology; Physical anthropology & ethnography; Organization & management of education; Education -- Administration -- General; Education -- Research